Studi Kasus: Foot Massage Minyak Zaitun untuk Fatigue pada Pasien Hemodialisis: Case Study: Foot Massage with Olive Oil for Fatigue Hemodialysis Patients - Nimsi Melati; Yohana Rambu Anarara Retang; Agustina Eka Kristiningsih (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Chronic kidney disease patients require dialysis therapy, one of which is hemodialysis. Fatigue is a side effect of hemodialysis. 71-92% of patients experience fatigue during hemodialysis. Fatigue is caused by the length of the hemodialysis process, anemia, uremia syndrome, and a decrease in blood pressure due to the effects of hemodialysis. Fatigue causes decreased concentration, emotional disturbances, and sleep disturbances which can affect daily activities and quality of life. The purpose of this research is to determine the effect of foot massage in reducing fatigue in hemodialysis patients. The research method uses quantitative descriptive with case studies. The sampling technique uses purposive sampling with a sample size of one person. The research measuring tool used the Functional Assessment Chronic Illness Therapy (FACIT) Fatigue Scale. The patient underwent three interventions, each intervention was carried out for 15 minutes during intra-hemodialysis. The results of the study showed that there was a reduction in fatigue from a moderate level to a mild level, which means that foot massage was able to reduce fatigue in chronic kidney failure patients who were undergoing hemodialysis. This is because foot massage can increase blood circulation which can increase the supply of oxygen and energy to the body and speed up the removal of metabolic waste from the body so that complaints of fatigue are reduced.